PERENCANAAN TITIK LAHAN PARKIR UMUM PADA KAWASAN KOMERSIAL JL. BOULEVARD DAN JL. PENGAYOMAN, KOTA MAKASSAR - Wahyuni, Arinda; Ahmad Nadhil Edar; Gusti Hardiyanti Musda (UNIVERSITAS STEKOM, 2023)
Jl. Boulevard and Jl. Pengayoman is a commercial area in Makassar City. Jl. Boulevard and Jl. Protection is quite strategic because it can be reached by all levels of society from various means of transportation. Various community activities such as walking, jogging, shopping, office activities, etc. have resulted in the increase in parking for visitors' vehicles in the area, covering the shoulders of the road and pedestrians. From the results of our previous research, it is clear that the cause of illegal parking that occurs in the commercial areas of Jalan Boulevard and Jalan Pengayoman is the limited parking space in each commercial building and the standard for calculating parking spaces in the commercial areas of Jalan Boulevard and Jalan Pengayoman. This is what causes the loss of user comfort and the change in pedestrian function to illegal parking in the Jl. Boulevard and Jl. Pengayoman is therefore an action that is contrary to Islamic Sharia which is haram because it is illegal, does not comply with local legal regulations and also harms other people. So, to restore the comfort and function of pedestrians in the commercial area of Jl. Boulevard and Jl. Pengayoman, we will carry out further research with the title